The epidermal growth factor receptor family: roles in development and cancer - Hynes, Nancy (Henry Stewart Talks, 2007)
ERBB receptor/ligand network, Activation and intracellular signaling, Developmental roles for ERBB2 containing heterodimers, ERBB receptor structure, Molecular alterations of ERBB receptors in cancer, Targeting ERBB receptors in cancer, In vivo and in vitro studies describing how ERBB receptor blockade impacts on cancer, Resistance of cancer cells to ERBB inhibitors
Archived at 2018/05/31